Carrot-Derived Rhamnogalacturonan-I Consistently Increases the Microbial Production of Health-Promoting Indole-3-Propionic Acid Ex Vivo - Mercenier, Annick; Vu, Lam Dai; Poppe, Jonas; Albers, Ruud; McKay, Sue; Van den Abbeele, Pieter (Metabolites, 2024)
Background: Using dietary interventions to steer the metabolic output of the gut microbiota towards specific health-promoting metabolites is often challenging due to interpersonal variation in treatment responses. Methods: In this study, we combined the ex vivo SIFR® (Systemic Intestinal Fermentation Research) technology with untargeted metabolite profiling to investigate the impact of carrot-derived rhamnogalacturonan-I (cRG-I) on ex vivo metabolite production by the gut microbiota of 24 human adults. Results: The findings reveal that at a dose equivalent to 1.5 g/d, cRG-I consistently promoted indole-3-propionic acid (IPA) production (+45.8% increase) across all subjects. At a dose equivalent to 0.3 g/d, increased IPA production was also observed (+14.6%), which was comparable to the effect seen for 1.5 g/d inulin (10.6%). IPA has been shown to provide protection against diseases affecting the gut and multiple organs. The Pearson correlation analysis revealed a strong correlation (R = 0.65, padjusted = 6.1 × 10−16) between the increases in IPA levels and the absolute levels of Bifidobacterium longum, a producer of indole-3-lactic acid (ILA), an intermediate in IPA production. Finally, the community modulation score, a novel diversity index, demonstrated that cRG-I maintained a high α-diversity which has previously been linked to elevated IPA production. Conclusions: The results from the ex vivo SIFR® experiment mirrored clinical outcomes and provided novel insights into the impact of cRG-I on the gut microbiome function. Importantly, we demonstrated that cRG-I promotes tryptophan conversion into IPA via gut microbiome modulation, thus conferring benefits via amino acid derived metabolites extending beyond those previously reported for short chain fatty acids (SCFA) resulting from carbohydrate fermentation.